A switchable circular polarizer based on zenithal bistable liquid crystal gratings. (14th April 2016) - Zografopoulos, Dimitrios C; Isić, Goran; Kriezis, Emmanouil E; Beccherelli, Romeo
Abstract: A switchable circular polarizer for infrared telecom wavelengths based on zenithal bistable liquid crystal gratings is designed and investigated by employing the finite-element method for the study of full-wave light propagation and a tensorial formulation for the liquid crystal orientation. The handedness of the output circular polarization can be selected by switching between the two stable states of the liquid-crystal grating. Analysis of the spectral dependence and the tolerance of the polarizer's performance with respect to deviations from the optimized geometry reveals the robustness of its polarizing properties, which stems from the non-resonant nature of its operation.